2021
DOI: 10.3350/cmh.2020.0204
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the management of intermediate-stage hepatocellular carcinoma: Current trends and prospects

Abstract: Hepatocellular carcinoma (HCC) is usually accompanied by chronic liver damage, which sometimes influences the selection of HCC treatment. The Barcelona Clinic Liver Cancer (BCLC) staging system, which was first introduced in 1999, is the most commonly used worldwide. Although the intermediate-stage (BCLC stage B) includes the largest number and heterogeneous HCC patients, the recommended treatment option is transarterial chemoembolization (TACE) only. However, recent progress in radical treatments such as hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 60 publications
(59 reference statements)
0
44
0
Order By: Relevance
“…Over the past decade, sorafenib (SOR), an oral multi-kinase inhibitor, has been the only anticancer agent to effectively improve overall survival (OS) [ 6 , 7 ]. Since 2018, lenvatinib (LENV), another oral multi-kinase inhibitor that targets vascular endothelial growth factor (VEGF) receptors, fibroblast growth factor (FGF) receptors, platelet-derived growth factor (PDGF) receptor-α, RET, and KIT, has been used as a first-line treatment option for unresectable HCC [ 8 ]. In the REFLECT study, the LENV arm showed a non-inferior OS compared to the SOR arm (median 13.6 vs. 12.3 months), in addition to a significantly improved progression-free survival (PFS; median 7.4 vs. 3.7 months, respectively; p < 0.001) and objective response rate (24.1% vs. 9.2%, respectively; p < 0.001) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, sorafenib (SOR), an oral multi-kinase inhibitor, has been the only anticancer agent to effectively improve overall survival (OS) [ 6 , 7 ]. Since 2018, lenvatinib (LENV), another oral multi-kinase inhibitor that targets vascular endothelial growth factor (VEGF) receptors, fibroblast growth factor (FGF) receptors, platelet-derived growth factor (PDGF) receptor-α, RET, and KIT, has been used as a first-line treatment option for unresectable HCC [ 8 ]. In the REFLECT study, the LENV arm showed a non-inferior OS compared to the SOR arm (median 13.6 vs. 12.3 months), in addition to a significantly improved progression-free survival (PFS; median 7.4 vs. 3.7 months, respectively; p < 0.001) and objective response rate (24.1% vs. 9.2%, respectively; p < 0.001) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In HCC patients with advanced stage, the long-term survival benefit from currently used anticancer treatments is a modest improvement of three months, which is far from satisfactory [ 6 , 7 , 16 , 17 ]. Clinically, there are critical limitations to treat HCC patients: (1) a lack of available drugs after failure of tyrosine kinase inhibitors [ 18 , 19 ]; (2) increasing need of target therapy agents in patients with intermediate stage who showed refractoriness for transarterial chemoembolization or inadequate safety margin of embolized area after TACE [ 12 , 17 , 20 , 21 , 22 , 23 , 24 ]; (3) substantial risk of HCC recurrence even after five years in patients who underwent curative resection [ 25 , 26 , 27 ]; (4) no available drugs for target therapy in patients with decompensated cirrhosis [ 28 ]. Therefore, there is a need to explore novel strategies as alternatives to the currently used drugs in patients with advanced HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Although more evidence is required, patients determined as being early stage B should be down staged and recommended curative treatment if possible. Furthermore, patients determined to have high-risk BCLC stage B and poor responders to TACE should be switched to targeted systemic therapies [ 26 , 27 ]. Additionally, although patients in our cohort had a smaller tumor burden, only 2% were determined to be stage 1 in the Pre-TACE-Predict models, which could indicate that the Pre-TACE-model is not adequate for identifying low-risk HCC patients.…”
Section: Discussionmentioning
confidence: 99%